Reception Analysis on the Representation of Jerusalem in Nas Daily Bahasa Indonesiaâ€™s â€œSindrom Yerusalem" - Irene Shendy Kharista; Edi Dwi Riyanto (Sosial Horizon: Jurnal Pendidikan Sosial, 2022)
The discourses related to Israel, Jews, and conflicts related to them in Indonesian media has an influence on how Indonesians view them, be it on the aspect of â€œIsraelâ€ as a nation, an ethnicity, or a religion. Nas Daily, a Facebook vlog account runs by an Israeli-Arab vlogger, uploaded an Indonesian version of one of his videos which talks about Jerusalem, a city part of Israel, in his Indonesian vlog Nas Daily Bahasa Indonesia.. Using Stuart Hall's theory of representation and theory of reception, this study aims to examine how Indonesian audiences respond to the representation of the city of Jerusalem in the video â€œSindrom Yerusalemâ€ produced by a Facebook vlog channel â€œNas Daily Indonesiaâ€. The analysis is done through a qualitative approach which is using the concepts in Hallâ€™s theories in order to do in-depth analysis on the readings of the audiences based on the comments found in the comment section of the video post. The findings on the analysis show how dominant reading on the video generally agree on the representation of Jerusalem as a city of spirituality and religiosity, which is presented positively in the video. On the other hand, most comments with oppositional reading relate their opinion based on the Israel-Palestine conflict, a context which is not mentioned in the video. Despite the disagreement on the positive representation, the oppositional readings still show the leaning on viewing Jerusalem and its related conflict through religious aspect, which is not so different from the aspect agreed upon by comments with dominant reading.